1999
DOI: 10.1080/07448489909595667
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Analysis of Students Seeking HIV Antibody Testing at a University Health Service

Abstract: The authors describe 255 students who voluntarily sought human immunodeficiency (HIV) antibody testing at a university health center. Fifty-nine percent of the students were women, their average age was 22.6 years, and they had low reported rates of unintended pregnancy and sexually transmitted diseases (STDs). Nearly one third of the students had been previously tested for HIV. Approximately 40% of students described sexual activities that placed them at some risk for HIV infection and other sexual problems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 14 publications
2
19
1
Order By: Relevance
“…Over 16 million of these people were women and about 1.4 million were children below the age of 15 years. Surveys conducted among university students in the United States and Tanzania showed that 59% and 55.9%, respectively, of students seeking voluntary counselling and testing (VCT) were women below the age of 25 years (Anastasi et al, 1999). The aim of VCT in pregnant women is to ensure that she does not become infected, or if she is already infected to institute intervention strategies to reduce the vertical transmission of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…Over 16 million of these people were women and about 1.4 million were children below the age of 15 years. Surveys conducted among university students in the United States and Tanzania showed that 59% and 55.9%, respectively, of students seeking voluntary counselling and testing (VCT) were women below the age of 25 years (Anastasi et al, 1999). The aim of VCT in pregnant women is to ensure that she does not become infected, or if she is already infected to institute intervention strategies to reduce the vertical transmission of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…22 Anastasi and colleagues reinforced the importance of HIV testing on college campuses, with 73% of the individuals seeking voluntary testing stating they would not have sought an HIV test had it not been offered through the college health center. These findings have been found previously in a sample of college students, with students indicating they would be more likely to seek testing if available on campus.…”
Section: Commentmentioning
confidence: 99%
“…These finding raise concerns about the need to increase HIV=AIDS prevention efforts and to develop strategies for empowering women of all cultures to engage in safe sex practices. This study and previous research of HIV=AIDS knowledge among college students has consistently shown that knowledge alone does not predict safe sex practices (Anastasi et al, 1999;Bates & Joubert, 1993;CDC, 2004;Gupta & Weiss, 1993, Lewis & Malow, 1997Opt & Loffredo, 2004). Within the three countries studied here, HIV=AIDS awareness among female college students is not associated with safer sex practices.…”
Section: Discussionmentioning
confidence: 51%
“…Research on HIV=AIDS knowledge among young people has consistently shown that knowledge alone does not predict safe sex practices (Anastasi, Sawyer, & Pinciaro, 1999;Bates & Joubert, 1993;CDC, 2008a;Gupta & Weiss, 1993, Lewis, Malow, & Ireland, 1997Opt & Loffredo, 2004). According to the gender and power theory (Connell, 1987;Wingood & DiClemente, 1996), women's risks of HIV infection are heavily influenced by socioeconomic factors, power imbalances within relationships, and gender-specific cultural norms.…”
mentioning
confidence: 95%